Alfvén Instabilities Excited by Energetic Particles in a Parameter Regime Similar to EAST Operation - 王军 胡纯栋 胡双辉 吴斌 丁斯晔 (Plasma science & technology, 2013)
The kinetic excitation of ideal magnetohydrodynamic （MHD） Alfvén instabilities is investigated for operations at the EAST tokamak. The instabilities include α-induced toroidal Alfvén eigenmodes （αTAE; here, α =-q2 Rdβ/dr, with q being the safety factor, β the ratio between the plasma and magnetic pressures, R the major radius, and r the minor radius）, toroidicity-induced Alfvén eigenmodes （TAE）, and the energetic particle continuum mode （EPM）. The αTAE, trapped by α-induced potential wells along the magnetic field line, can be readily destabilized by energetic particles due to negligible continuum damping via wave energy tunneling. It is shown for the geometry and the parameters similar to those of the EAST equilibrium that αTAE is different not only from the EPM by the potential-well determined frequency, but also from the TAE by the broad frequency spectrum outside the toroidal frequency gap.